Evaluation of Touristic Risks While Visiting Ukraine and the Risk Perception by Travelers - HORIACHKO, Kateryna (Journal of Environmental Management and Tourism; Vol 12 No 1 (2021): JEMT 1(49) Spring 2021DO - 10.14505/jemt.12.1(49).11, 2021)
International tourist arrivals increase every year. Ukraine has always been a popular country for spending a vacation. However, many foreign tourists have very bad expectations about the trip to Ukraine. The reason is the military conflict in the East of the country. This article aims to explain whether Ukraine is a risky destination for tourists. For this purpose the determination, estimation and prediction of the risks for tourists in the summer of 2018 was conducted. This study shows that the risk is the main motivation of traveller’s destination choice. The methodology to assess risks for foreign tourists who visit Ukraine is proposed in the article. To confirm the tourist threats evaluation model, an investigation was conducted, which included gathering information about potential touristic risks. The list of probably dangerous and mid-level dangerous touristic risks was determined in the summer n of 2019 in Ukraine. The fact that trips to the territory of Ukraine are safe was established.